Implementation of a unique hepatitis C care continuum model in Rwanda. (6th July 2018) - Mathur, Poonam; Comstock, Emily; Makuza, Jean Damascene; Emmanuel, Benjamin; Sebeza, Jackson; Kiromera, Athanase; Wilson, Eleanor; Kattakuzhy, Sarah; Nelson, Amy; Kottilil, Shyamasundaran; Riedel, David J
Abstract: Background: There has been an evolution in the treatment of chronic hepatitis C (HCV) due to highly effective direct-acting antivirals, however, restriction of treatment to medical specialists hinders escalation of HCV treatment. This is particularly true in resource-limited settings (RLS), which disproportionately represent the burden of HCV worldwide. The ASCEND study in Washington, DC, demonstrated that complete task-shifting can safely and effectively overcome a low provider-to-patient ratio and expand HCV treatment. However, this model has not been applied internationally to RLS. Method: The validated ASCEND model was translated to an international clinical program in Kigali, Rwanda, aimed at training general medicine providers on HCV management and obtaining HCV prevalence data. Results: The didactic training program administered to 11 new HCV providers in Rwanda increased provider's knowledge about HCV management. Through the training program, 26% of patients seen during the follow-up period were screened for HCV and a prevalence estimate of 2% was ascertained. Of these patients, 30% were co-infected with hepatitis B. Conclusion: The ASCEND paradigm can be successfully implemented in RLS to escalate HCV care, in a self-sustaining fashion that educates more providers about HCV management, while increasing the public's awareness of HCV and access to treatment.